2002
DOI: 10.1038/sj.onc.1205791
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Wnt-1 or Wnt-3a of nerve growth factor-induced differentiation of PC12 cells is reversed by bisindolylmaleimide-I but not by several other PKC inhibitors

Abstract: Wnt-1 and Wnt-3a exhibit redundancy in neural crest development. We have found that they do not produce the same effects on PC12 cells, which were obtained from the adrenal medulla, a neural crest derivative. However, both Wnt-1 or Wnt-3a inhibit nerve growth factor (NGF)-induced neurite outgrowth. The inhibition is reversed by the protein kinase C (PKC) inhibitor, bisindolylmaleimide-I, but it did not reverse Wnt-1-induced activation of the canonical Wnt pathway. The Wnt-1 inhibitory effect was not reversed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Optimedin's action on stimulated PC12 cells in some respects resembles action of Wnt proteins [25][26][27][28]. Similar to optimedin expression, expression of Wnt1 or Wnt3a cDNAs in PC12 cells inhibited NGF-induced differentiation PC12 cells and neurite growth.…”
Section: Optimedin Does Not Stimulate Tcf/lef Signalingmentioning
confidence: 86%
See 1 more Smart Citation
“…Optimedin's action on stimulated PC12 cells in some respects resembles action of Wnt proteins [25][26][27][28]. Similar to optimedin expression, expression of Wnt1 or Wnt3a cDNAs in PC12 cells inhibited NGF-induced differentiation PC12 cells and neurite growth.…”
Section: Optimedin Does Not Stimulate Tcf/lef Signalingmentioning
confidence: 86%
“…Optimedin, similar to some other secreted glycoproteins, may interact with cellular receptor(s) and stimulates or inhibits cellular signaling pathways. Altough optimedin's action on stimulated PC12 cells in some respects resembles action of Wnt proteins [25][26][27][28], optimedin does not stimulate the canonical Wnt pathway through TCF/LEF signaling (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Wnt-1 or Wnt-3a in PC12 cells inhibits NGF-induced neurite outgrowth (11,47). The effects of targeted inactivation of Wnt-1 and Wnt-3a in mice suggest their critical role in neuronal development, including remodeling of the axon (23).…”
Section: Discussionmentioning
confidence: 99%
“…Wnts are secretory proteins of ∼40 kDa that control multiple aspects of development, including the proliferation, fate specification, polarity, and migration of cells 6566. In addition, Chou et al reported that Wnt-1 and Wnt-3a both inhibit NGF-induced neurite outgrowth from PC12 cells 67. These results showed that sensory nerve receptors and neurotrophic markers cooperate with Wnt signals in regulating many biological processes, but the mechanisms of their interaction remain poorly defined in the IVD.…”
Section: Effect Of Degenerative Changes On Intervertebral Disk Cell Smentioning
confidence: 99%